Effect of chronic cold stress and dalargin on blood parameters in guinea pigs - Myrnyi, Vladyslav; Moisieieva, Nataliia (Problems of Cryobiology and Cryomedicine, 2026)
This study investigates the effects of the synthetic neuropeptide dalargin on hematological parameters and blood electrolyte homeostasis in guinea pigs under conditions of chronic cold stress (CCS) at 4°C over a five-day period. It was found that CCS led to a reduction in platelet count and disruption of the leukocyte profile, including an increase in band neutrophils accompanied by a decrease in segmented neutrophils, lymphocytes, and monocytes, as well as a decline in the adaptation index. Simultaneously, elevated concentrations of calcium, potassium, and chloride were observed, indicating disturbances in electrolyte balance and ionic homeostasis. Dalargin administration prevented these changes, promoting the restoration of physiological leukocyte ratios, increasing platelet counts, and normalizing key plasma electrolyte concentrations. Moreover, an increase in the adaptation index was recorded, indicating activation of the hematopoietic system and mobilization of the organism’s adaptive potential These findings support the potential of dalargin as an effective agent for maintaining blood system integrity, electrolyte balance, and adaptive capacity under CCS conditions. Probl Cryobiol Cryomed. 2025; 35(3): 115—122